Meat Quality of Land Crab, Cardiosoma armatum (Herklots, 1851) Fattened with Trash Fish and Formulated Diet (Journal of Scientific Research, 2020)
Meat quality in terms of its nutritional value, is a major factor when considering dietary items. This study highlighted the proximate and mineral compositions in the meat of Land Crab, Cardiosoma armatum (Herklots, 1851) fed with Trash Fish (Natural feed) and formulated diet for three (3) months. The meat proximate composition of both crabs fed the two different diets was similar, and there was no significant difference in the crude protein, fat and fiber contents of the meat (p > 0.05). The diets had no significant effects on magnesium, sodium, potassium and phosphorus contents of the meat. Crabs fed formulated diet had significantly higher calcium content of 20428.52±0.10 mg/100 g, compared with the crabs fed with Trash Fish of 18541.83±0.10 mg/100 g (p < 0.05). The pattern of mineral contents in both crabs was calcium > phosphorus > magnesium > sodium > potassium. This study suggested no negative effects of formulated diet on the meat quality. Therefore, formulated diet could be used for fattening of Land Crabs.